Giant Sweetpotato Bug, Spartocera batatas (Fabricius) (Insecta: Hemiptera: Coreidae) - Susan E. Halbert (EDIS)
A large colony of Spartocera batatas (Fabricius) was found in late June 1995 on an Asian cultivar of sweet potatoes (Ipomoea batatas) in Homestead, Florida, by Lynn D. Howerton, environmental specialist, Division of Plant Industry (DPI). The plants were badly damaged by the insects. That collection represented the first report of S. batatas in the continental U.S. Subsequent surveys of commercial fields of sweet potatoes in the area failed to turn up any more S. batatas. However, an additional single specimen was found in Miami in early October 1995 by DPI Inspector Ramon A. Dones. Many bugs were found in suburban Miami by Julieta Brambila (University of Florida, Institute of Food and Agricultural Sciences) in late September 1996. This document is EENY-305 (originally published as DPI Entomology Circular 379), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2003.